Advances in the Management of Acute Venous Thromboembolism and New Therapeutic Agents - Stevens, Hannah; McFadyen, James; Chan, Noel (Seminars in Respiratory and Critical Care Medicine, 2021)
Important advances in the understanding and management of venous thromboembolism (VTE) have enhanced our ability to diagnose, prevent, and treat VTE. In this narrative review, we discuss how recent advances in the understanding and management of VTE are changing practice, highlight ongoing unmet needs in VTE management, and outline how novel therapeutic targets with little or no influence on hemostasis may help address these unmet needs.
Keywords: venous thromboembolism; pulmonary embolism; deep vein thrombosis; direct oral anticoagulants; diagnosis